1999
DOI: 10.1175/1520-0485(1999)029<3133:maqdvo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Multi- and Quasi-Decadal Variations of Sea Surface Temperature in the North Atlantic

Abstract: The multi-and quasi-decadal variabilities of the sea surface temperature (SST) anomaly over the North Atlantic are investigated by means of two-dintensional propagating CEOR Forty-six years of the COADS SST dataset from 1947 to 1992 are used. After removing the monthly climatology and four-year low-pass filtering the SST anomaly is submitted to CEOR The total variance of the three largest modes accounts for 87.0% of the total variance. Mode 1 is a very slow oscillation with an approximate 42-yr period and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…However, the lack of an authoritative consensus definition of the AMO in the scientific literature to date precludes us from definitively claiming that the leading mode and the AMO are one and the same. PC2 has spectral energy concentrated in the 6-14 year period (Figure 1(e)), in agreement with the work of Mizoguchi et al (1999).…”
Section: North Atlantic Variabilitysupporting
confidence: 86%
See 3 more Smart Citations
“…However, the lack of an authoritative consensus definition of the AMO in the scientific literature to date precludes us from definitively claiming that the leading mode and the AMO are one and the same. PC2 has spectral energy concentrated in the 6-14 year period (Figure 1(e)), in agreement with the work of Mizoguchi et al (1999).…”
Section: North Atlantic Variabilitysupporting
confidence: 86%
“…The third and higher-order modes are not discussed in the present examination to highlight the modes clearly associated with the AMO and the NAO only. Some EOF analyses (namely Mizoguchi et al, 1999) of North Atlantic SST have found a quasi-decadal signal manifesting itself as the splitting of modes 2 and 3; this did not occur in the present examination. Subsequently, the two PC time series were each detrended and scaled by their respective standard deviations.…”
Section: Methodscontrasting
confidence: 64%
See 2 more Smart Citations
“…They also identified another 7-8-yr oscillation, which involves the entire double-gyre circulation of the North Atlantic. Enfield and Mestas-Nuñez (1999) summarized the classic features normally associated with the Pacific ENSO mode as follows: (i) a region of intense amplitude within Ϯ10°o f the equator and east of the date line, which decreases to small amplitude over a wide, wedge-shaped region 3 Multidecadal NA 3 Interdecadal Eastern NP 3 Interdecadal Eastern TP 3 Interdecadal Central TP 3 Multidecadal NP 3 Interannual to interdecadal SA Mizoguchi et al (1999) COADS ( Lohmann and Latif (2005).…”
Section: Introductionmentioning
confidence: 99%